Manual del cultivo de café en el VRAEM - Montañez Ártica, Ana Gabriela; Arias Ricaldi, Joab Nazario; Ayala Salcedo, Wenceslao; Carrera Rojo, Ronald Pio; Dávila Pérez, Jesús; Campos Tello, Jaime Danini; Huacce Prado, Reíder; Hermoza Gamarra, Yuri; Ruiz Medina, Fredy; Flores Gutiérrez, Milton Medardo; Altamirano Pareja, Miraldino (Instituto Nacional de Innovación Agraria, 2022)
50 páginas